Is delirium after stroke associated with dysregulation of hypothalamic pituitary axis? - Barugh, Amanda J.; MacLullich, Alasdair M. J.; Shenkin, Susan S.; Allerhand, Michael; Mead, Gillian E. (Frontiers in Stroke, 2025)
Delirium after stroke is a serious condition associated with worse long-term cognition. However, the mechanism of delirium is not well understood. The aberrant stress response has been postulated as a mechanism for delirium.Aimto explore the relationship between cortisol dysregulation and delirium over the first year after stroke in a prospective cohort study of patients admitted to an acute stroke unit.Methodsconsecutive patients admitted to an acute stroke unit over a 1 year period were identified and recruited if they were aged age ≥ 60 years and not taking steroids. Patients with incapacity were included if proxy consent could be obtained. Baseline data included stroke severity, cognition, illness severity, and pre-stroke cognition. Patients were assessed at 1, 3, 5, 7, 14, 21, 28 days, 4 months and 12 months for delirium. Salivary samples were taken morning and evening for cortisol analysis.Resultsof the 831 patients screened, 304 met inclusion criteria and of these 95 agreed to participant. Twenty-six (27%) had delirium at some point during the 12 months follow-up. Delirium was associated with increasing age (mean age 83.5 years vs. 74 years, p < 0.001), being female (62% vs. 23%, p = 0.013), not independent in pre-stroke activities of daily living (35% vs. 33%), higher IQCODE score median 3.56 vs. 3.19), worse stroke severity (median National Institute of Stroke Scale 5 vs. 8.5) p = 0.009) and having had a total anterior circulation stroke (p < 0.001). Univariable analyses identified several associations between delirium and cortisol in the first 28 days but not at 4 or 12 months. However, on multivariable analyses there were no significant associations between delirium and cortisol at any time point, e.g., odds ratio for median 9 am cortisol 0.95 (95% CI 0.89 to 1.01, p = 0.08).Conclusionthere was no independent association between delirium and cortisol dysregulation after stroke. If an association does exist, it is likely to be small.